(untitled) (Iranian Journal of Kidney Diseases, 2020)
Treatment of coronavirus disease 2019 (COVID-19) among patients with CKD requires special pharmacotherapy considerations that are reviewed here. Literature review was done for several pharmacotherapy aspects in CKD patients including selection and modification of COVID-19 treatment, drug interactions, nephrotoxicity of drugs that are used for treatment of COVID-19 and potential risks/benefits of routine medications of CKD patients during COVID-19 pandemic. CKD patients should be treated according to local or national COVID-19 protocols as other patients. But, there is no data on using remdesivir in patients with severe CKD. Oseltamivir and ribavirin require dose modification in patients with moderate to severe CKD. Nephrolithiasis, CKD, and acute interstitial nephritis have been reported with protease inhibitors. Acute kidney injury has been reported with remdesivir in patients with severe COVID-19. Pharmacokinetic-enhanced protease inhibitors increase the concentration of some drugs such as statins, cinacalcet, steroids, calcineurin inhibitors (CNIs). Some hypothetical benefits and harms have been suggested for statins and renin-angiotensinaldosterone system inhibitors in COVID-19 patients. Continuing guideline-directed administration of these drugs is recommended. Among different immunomodulating/immunosuppressive drugs, hydroxychloroquine and CNIs are the safest ones during COVID-19. Antimetabolites are suggested to be withheld during moderate to severe COVID-19. Fluid therapy and anticoagulant prophylaxis/ treatment need special attention in CKD patients with COVID-19. CKD patients with COVID-19 are treated as other patients, with some dose modifications if needed. Be mindful for management of drug interactions as well as modification of immunosuppressive drugs in patients with moderate to severe COVID-19.